13C-mixed triglyceride CO2 exhalation test. Investigation with an isotope selective, non dispersive infrared spectrophotometer of indirect function of the exocrine pancreas - Adamek, R J; Bödeker, C; Szymanski, C; Hagemann, D; Pfaffenbach, B (Deutsche medizinische Wochenschrift, 1999)
The 13C-mixed-triglyceride CO2-exhalation test (MTE) has been proposed for the noninvasive assessment of intraluminal duodenal pancreatic lipase activity. Up to now, stable isotope analysis of carbon dioxide of the MTE has been carried out with isotope ratio mass-spectrometry. The aim of the present study was to evaluate the MTE in patients with morphological signs of chronic pancreatitis (stages I-III) and exocrine pancreatic insufficiency by using an isotope-selective nondispersive infrared spectrometer (NDIRS). 20 healthy volunteers (9 females, 11 males, age range 19-61 years) and 16 patients (7 females, 9 males, age range 33-76 years) were examined. After an overnight fast each patient received a solid-liquid test meal containing 250 mg 1,3 distearyl, 2[13C] octanoyl glycerol. Breath samples were obtained at baseline and at 30 min intervals over a period of 6 h after the test meal. The 13C/12C isotope ratio in each breath sample was determined by NDIRS as delta (%) and delta over baseline (%). Results were expressed as cumulative percentage dose of 13C recovered (cPDR) at 3, 4, 5, 6 h and maximal PDR (PDRpeak) (median; 5./95. percentile). Significant lower values concerning cPDR 3, 4, 5, 6 hours and PDRpeak [%] were found between healthy subjects and patients with chronic pancreatitis (p < 0.05): cPDR 6 h: 8.1 (0.4-20.5)% vs 29.1 (10.3-59.3)%; PDRpeak: 4.7 (0.4-10.2)% vs 9.2 (5.4-14.3)%. In general, the MTE discriminates between healthy controls and patients with chronic pancreatitis and exocrine pancreatic insufficiency. However, the MTE using NDIRS cannot be recommended as a method of clinical routine because of marked data overlap between pathologic and normal values.